Réflexions sur la dichotomie entre néolocuteurs et locuteurs natifs/traditionnels dans le cadre de la revitalisation des langues minoritaires : vers un nouveau discours inclusif - Robert Neal Baxter (Lengas)
The phenomenon of newspeakerism is discussed within the context of minority languages in the light of the native/non-native speaker dichotomy. Tracing the colonial origins of the concept of the native speaker reveals how the divide is underpinned by an exclusivist narrative based on accident of birth, leading to a consensus within second language teaching for the need to overcome what is described as a racist ideology. The concepts of legitimacy and ownership highlight how the analogous traditional/new speaker dichotomy can replicate and perpetuate divides within minority speech communities, potentially hindering revitalisation efforts. The paper concludes that new speakers should be granted a sense of linguistic entitlement whilst avoiding side-lining traditional speakers, calling for a paradigm shift putting all speakers on an equal footing based on their linguistic proficiency and level of commitment to language maintenance in order to strengthen revitalisation efforts.